Advances in preclinical assessment of therapeutic targets for bladder cancer precision medicine - Nössing, Christoph; Herek, Paula; Shariat, Shahrokh F; Berger, Walter; Englinger, Bernhard (Current opinion in urology, 2024)
PURPOSE OF REVIEW: Bladder cancer incidence is on the rise, and until recently, there has been little to no change in treatment regimens over the last 40 years. Hence, it is imperative to work on strategies and approaches to untangle the complexity of intra- and inter-tumour heterogeneity of bladder cancer with the aim of improving patient-specific care and treatment outcomes. The focus of this review is therefore to highlight novel targets, advances, and therapy approaches for bladder cancer patients. RECENT FINDINGS: The success of combining an antibody-drug conjugate (ADC) with immunotherapy has been recently hailed as a game changer in treating bladder cancer patients. Hence, interest in other ADCs as a treatment option is also rife. Furthermore, strategies to overcome chemoresistance to standard therapy have been described recently. In addition, other studies showed that targeting genomic alterations (e.g. mutations in FGFR3 , DNA damage repair genes and loss of the Y chromosome) could also be helpful as prognostic and treatment stratification biomarkers. The use of single-cell RNA sequencing approaches has allowed better characterisation of the tumour microenvironment and subsequent identification of novel targets. Functional precision medicine could be another avenue to improve and guide personalized treatment options. SUMMARY: Several novel preclinical targets and treatment options have been described recently. The validation of these advances will lead to the development and implementation of robust personalized treatment regimens for bladder cancer patients.
Keywords: nádorové biomarkery; Immunoconjugates; Tumor Microenvironment; Biomarkers, Tumor; nádory močového měchýře; individualizovaná medicína; lidé; cílená molekulární terapie; Molecular Targeted Therapy; Immunotherapy; Urinary Bladder Neoplasms; imunokonjugáty; nádorové mikroprostředí; Precision Medicine; Humans; imunoterapie